Notes on Latin American Philosophy and Analogical Hermeneutics: An Interview with Mauricio Beuchot - Machado Mota, Bento (Sofia, 2026)
This interview with Professor Mauricio Beuchot explores his proposal for advancing analogical hermeneutics and discusses both the history of Latin American Philosophy and interdisciplinary connections within the broader field of Philosophy.
Keywords: hermeneutic; latin american philosophy